Automeris (Lepidoptera: Saturniidae) stinging larvae in Cajanus cajan: a health risk for Panamanian farmers - Santos-Murgas, Alonso (2022)
Objective. To Identify the stinging larvae species complex of the genus Automeris Hübner, 1819 (Lepidoptera: Saturniidae), associated with pigeon pea crops, Cajanus cajan (L.), that represent a health risk for farmers in Panama. Methods. The study is descriptive and exploratory. During the second semester of 2022, trips were made in areas with pigeon pea crops in the provinces of Coclé, Herrera, Veraguas and Chiriquí. A photographic record was kept and specimens were collected, which were prepared with boiling water and then deposited in glass vials with 70 % ethanol. The laboratory identifcation of the specimens was made by consulting specialized literature. Results. Three larvae species of the genus Automeris associated with pigeon pea crops were identifed: Automeris zozine Druce, 1886, and Automeris dagmarae Brechlin & Meister, 2011, in the province of Chiriquí; Automeris io Fabricius, 1775, in the province of Coclé. The genus Automeris belongs to the subfamily Hemileucinae; which includes severalspecies of poisonous larvae that can represent a health risk, such as Lonomia obliqua Walker, 1855, commonly known as the assassin caterpillar. Conclusions. Three species of stinging larvae of the genus Automeris (Lepidoptera:  Saturniidae: Hemileucinae) were identifed, which represent a farmers’ health risk in Panama.